1999
DOI: 10.1021/ie9807396
|View full text |Cite
|
Sign up to set email alerts
|

Production of Hydrogen Peroxide in Liquid CO2. 2. Catalytic Hydrogenation of CO2-philic Anthraquinones

Abstract: Pd-catalyzed hydrogenations of fluoroether-functionalized anthraquinones (FAQs) were conducted in liquid CO 2 (P ) 235 bar) at room temperature. The kinetics of the hydrogenation of the FAQs in liquid CO 2 was investigated in a high-pressure batch reactor under a 10-fold excess of hydrogen, while varying the catalyst loading and catalyst particle size. The pressures employed were such that H 2 , CO 2 , and FAQ formed a single phase. The 1 H NMR analysis of the FAQs after a hydrogenation-oxidation cycle showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Production of Hydrogen Peroxide in CO 2. Production of hydrogen peroxide based on the anthraquinone−anthrahydroquinone process is an ideal target for CO 2 technology . First, the replacement of the organic solvent with CO 2 will eliminate the organic contamination of the aqueous product during the extraction stage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Production of Hydrogen Peroxide in CO 2. Production of hydrogen peroxide based on the anthraquinone−anthrahydroquinone process is an ideal target for CO 2 technology . First, the replacement of the organic solvent with CO 2 will eliminate the organic contamination of the aqueous product during the extraction stage.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalized anthraquinones (FAQs) exhibit liquid−liquid phase behavior with a minimum miscibility pressure that varies significantly with the structural parameters of the FAQ. We concluded that generation of FAQs with several short CO 2 -philic tails linked to anthraquinone by ether, C−C, or N−C links would provide the best phase behavior results 9a 1 Functionalized anthraquinones (Kr, poly(perfluoropropylene oxide) polymer). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palladium-catalyzed reactions such as hydrogen production, hydrogenation, and the Heck reaction have attracted much attention because of their importance to clear energy development and organic synthesis applications. , Although many Pd(0)-based catalysts are well established, catalyst separation and enhancement of catalytic activity are still large challenges and continue to be the focus of intense research. Over the last three decades, several elegant approaches have been explored to overcome the limitation of catalyst separation, for example, aqueous and fluorous biphase catalysis, reactions in supercritical media, and catalyst immobilization onto solid supports …”
mentioning
confidence: 99%
“…In search of the n‐type redox sites to bind to the non‐conjugated main chain, we focus on anthraquinone (AQ) derivatives based on the following characteristics: (i) the 2e − reaction for the ultimate charging (AQ + 2e − = AQ 2− ) that allows the charge storage with the closed‐shell system and leads to the inherently large storage density,27–29 (ii) the robustness that withstand high levels of labile atmospheres during the well‐known anthraquinone process for the production of H 2 O 2 ,30–34 and (iii) the suitable redox potentials in the range of −0.5 to −1 V versus Ag/AgCl35, 36 which is more negative than those of the p‐type organic cathode‐active materials such as poly(1‐oxy‐2,2,6,6‐tetramethylpiperidin‐4‐yl methacrylate) (PTMA) and poly(1‐oxy‐2,2,6,6‐tetramethylpiperidin‐4‐yl vinyl ether) (PTVE) near +0.8 V37–58 and yet sufficiently more positive than that of the Li anode 59–61. A number of anthraquinone polymers have been examined as the electode‐active materials,62–65 but most of them are π‐conjugated and/or main chain‐type polymers66–70 rather than those containing anthraquinone pendants, resulting in the lower capacities than their theoretical densities and low rate performances due to the limited mass transfer process through the slab of the rigid and crystalline conjugated polymer layers.…”
Section: Introductionmentioning
confidence: 99%